Johann Gottfried Herder and the Latvian voice - Jaremko-Porter, Christina (The University of Edinburgh, 2009)
As a young émigré from Königsberg to Riga Johann Gottfried Herder (1744—1803) developed a lifelong interest in the oral poetry of the common people, whose popular song traditions he later entitled Volkslieder. Herder’s affirmation of aesthetic and cultural individuality in his landmark collection of that title (1778-79) had far-reaching implications for the evolution of Latvian and East European folksong scholarship, and these extend to the practices of the present day. Underlying this work are source readings in translation that have been important in considering Herder’s prevailing influence. Pivotal historical episodes demarcate, first, Herder’s philosophical ties to the late nineteenth-century Latvian national awakening, second, to the final years of dissent within the Latvian Soviet Socialist Republic, and finally, to the current practitioner groups (kopas) that espouse ethnic and regional song traditions in a changing cultural milieu. A demonstration from each of Latvia’s four provinces has formed the substance of interviews and recordings in a fieldwork inquiry, which dates from 2000 to 2007. The conclusion evaluates Herder’s cyclical philosophy of history and humanity (Humanitätsideal) in relation to the diverse voices of Latvia’s ethnic minorities.
Keywords: Johann Gottfried Herder